Shareholders’ protection through the enhanced independent advice circular - Ambaras Khan, Mushera Bibi (Sweet & Maxwell, 2011)
Shareholders of a target company must be well informed of the merits of a takeover bid for their shares. The takeovers law requires the board of the bidder to provide all information necessary to enable the shareholders of the target to arrive at an informed decision. In addition, the board of the target company is also required to appoint an independent adviser to assist the shareholders in making their decision. The Securities Commission Malaysia (SC) has published a consultation paper in March 2010 with the aim of improving the quality of independent advice circulars. The SC suggests that when arriving at its opinion, an independent adviser should see that the takeover bid is “fair” and “reasonable”. The SC chooses to adopt the Australian approach which decouples the terms “fair and reasonable”. This article examines the criteria which are laid down by the SC for an offer to be “fair” and “reasonable”. It also examines the contents of independent advice circulars in Malaysia and their usefulness to the shareholders when assessing the merits of the bid.